Post-error action control is neurobehaviorally modulated under conditions of constant speeded response - Soshi, Takahiro; Ando, Kumiko; Noda, Takamasa; Nakazawa, Kanako; Tsumura, Hideki; Okada, Takayuki (Frontiers in Human Neuroscience, 2015)
Post-error slowing is an error recovery strategy that contributes to action control, and occurs after errors in order to prevent future behavioral flaws. Error recovery often malfunctions in clinical populations, but the relationship between behavioral traits and recovery from error is unclear in healthy populations. The present study investigated the relationship between impulsivity and error recovery by simulating a speeded response situation using a Go/No-go paradigm that forced the participants to constantly make accelerated responses prior to stimuli disappearance (stimulus duration: 250 ms). Neural correlates of post-error processing were examined using event-related potentials (ERPs). Impulsivity traits were measured with self-report questionnaires (BIS-11, BIS/BAS). Behavioral results demonstrated that the commission error for No-go trials was 15%, but post-error slowing did not take place immediately. Delayed post-error slowing was negatively correlated with error rates and impulsivity traits, showing that response slowing was associated with reduced error rates and changed with impulsivity. Response-locked error ERPs were clearly observed for the error trials. Contrary to previous studies, error ERPs were not significantly related to post-error slowing. Stimulus-locked N2 was negatively correlated with post-error slowing and positively correlated with impulsivity traits at the second post-error Go trial: larger N2 activity was associated with greater post-error slowing and less impulsivity. In summary, under constant speeded conditions, error monitoring was dissociated from post-error action control, and post-error slowing did not occur quickly. Furthermore, post-error slowing and its neural correlate (N2) were modulated by impulsivity traits. These findings suggest that there may be clinical and practical efficacy of maintaining cognitive control of actions during error recovery under common daily environments that frequently evoke impulsive behaviors.